Increased Competitive Fitness of Bacillus subtilis under Nonsporulating Conditions via Inactivation of Pleiotropic Regulators AlsR, SigD, and SigW - Nicholson, Wayne L. (American Society for Microbiology, 2012)
Previous studies implicated loss of motility and mutations of the alsR and sigW regulatory genes in enhanced fitness of the Bacillus subtilis evolved strain WN716 over that of its ancestral strain WN624. The fitness of strains carrying knockout mutations alsR::spc, sigD::kan, and/or sigW::erm was measured and compared to that of the congenic ancestral strain by competition experiments.